2022
DOI: 10.1093/hmg/ddac082
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of DNA replication timing across 184 cell lines suggests a role forMCM10in replication timing regulation

Abstract: Cellular proliferation depends on the accurate and timely replication of the genome. Several genetic diseases are caused by mutations in key DNA replication genes; however, it remains unclear whether these genes influence the normal program of DNA replication timing. Similarly, the factors that regulate DNA replication dynamics are poorly understood. To systematically identify trans-acting modulators of replication timing, we profiled replication in 184 cell lines from three cell types, encompassing 60 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…In chondrocytes, upregulation of CDC20 and TOP2A might be an indication of insufficient compensatory cartilage and bone regeneration capacity in response to the destruction of cartilage and subchondral bone. Furthermore, MCM10, a highly conserved pre-replication complex, was recently reported to be a modulator of DNA replication timing ( 20 ), suggesting that it plays a potential regulatory role in chondrocyte survival in OA at a deeper genetic level. In addition, another important aspect of OA is the synovial change ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In chondrocytes, upregulation of CDC20 and TOP2A might be an indication of insufficient compensatory cartilage and bone regeneration capacity in response to the destruction of cartilage and subchondral bone. Furthermore, MCM10, a highly conserved pre-replication complex, was recently reported to be a modulator of DNA replication timing ( 20 ), suggesting that it plays a potential regulatory role in chondrocyte survival in OA at a deeper genetic level. In addition, another important aspect of OA is the synovial change ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…A crucial part of cell proliferation is the replication of DNA that occurs during S phase of the cell cycle and is recognized as a vital biological activity for preserving the stability and integrity of the genome. Recent study into the regulation of replication timing has demonstrated that MCM10 mutations are associated to significant replication timing variations [3]. In addition, MCM10 has also been shown to interact with ssDNA and various critical DNA replication proteins including CDC45, MCM2-7, DNA polymerase, PCNA, and GINS [7][8][9][10][11], all of which are required for accurate cell replication and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A central part of cell proliferation is the replication of DNA that happens during S phase of the cell cycle. Recent research into the regulation of replication timing has found that MCM10 mutations are linked to extensive replication timing variations [3]. It has been reported that cells from a single patient with MCM10 mutations showed replication time variability in 46 percent of the genome, compared to RIF1 knockdown (a known modulator of replication timing) [3].…”
Section: Mcm10 Overexpression Induces Significant Increase In Prolife...mentioning
confidence: 99%
See 2 more Smart Citations